The cost of living in Notosuchia (Crocodyliformes, Mesoeucrocodylia) - Sena, Mariana Valéria de Araújo; Montefeltro, Felipe C. [UNESP]; Marinho, Thiago S.; Langer, Max C.; Fachini, Thiago S.; Pinheiro, André E. Piacentini; Machado, Alessandra S.; Lopes, Ricardo T.; Pellarin, Romain; Sayão, Juliana M.; Oliveira, Gustavo R.; Cubo, Jorge (Elsevier, 2023)
Limbs of terrestrial notosuchian crocodyliforms are characterized by a permanent parasagittal position similar to that of mammals and dinosaurs. Thus, we expect high maximal rates of oxygen consumption (i.e., high aerobic capacities). To test this hypothesis, we inferred mass-independent maximal metabolic rates (MMRs) in seven notosuchian species using the femur blood flow rate (Q̇; cm3 s−1) correlated with the maximal metabolic rate as a proxy. We employed a phylogenetic eigenvector maps (PEMs) inference model based on 20 extant tetrapod species. Generally, ectothermic amniotes have lower maximal metabolic rates than similarly sized endotherms. However, certain anatomical features of the cardiorespiratory system in varanid lizards enable them to develop a more active lifestyle than other ectothermic sauropsids. We found that the retrodicted mass-independent aerobic capacity values for Notosuchia are significantly lower than those measured in mammals and varanid lizards sampled but significantly higher than those quantified in Crocodylia. Notosuchians exhibit Q̇ values on the femoral shaft higher than Crocodylus porosus, suggesting greater oxygen consumption during intense exercise, but significantly lower than those measured in varanid lizards. This condition probably allowed notosuchians to engage in prolonged strenuous locomotion activities, such as hunting prey, defending themselves from predators or avoiding competitors. The evolution of Mesoeucrocodylia metabolism involves at least two phenotypes, a relatively high (Notosuchia) and a low (Neosuchia, Crocodylia) MMR. Significance statement: We modeled three-dimensional (3D) objects from Notosuchia femora and conducted measurements on the nutrient foramina size. These values were used as a proxy to infer the blood flow rate (Q̇) and provided insights into the maximal metabolic rate in these terrestrial crocodyliforms. Our findings suggest that Notosuchia were likely ectotherms, but exhibited a more active lifestyle than extant Crocodylia. However, they had aerobic capacities significantly lower than those measured in varanid lizards.
Keywords: Aerobic metabolism; Maximum metabolic rate; Non-avian sauropsids; Notosuchians; Phylogenetic eigenvectors